2021
DOI: 10.3389/fendo.2021.665717
|View full text |Cite
|
Sign up to set email alerts
|

Serum Progesterone Profile Across the Mid and Late Luteal Phase in Artificial Cycles Is Associated With Pregnancy Outcome

Abstract: IntroductionRecent studies have shown that low serum progesterone levels on the day of embryo transfer (ET) are associated with poorer pregnancy outcome in hormonal replacement therapy cycles. It is of interest to know if serum progesterone levels during late luteal phase (following days after ET) are also related with the chances of ongoing pregnancy.ObjectiveTo evaluate the luteal phase endocrine profile through measurements of serum progesterone and estradiol on days ET+4, ET+7 and ET+11, to test their pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, if P levels are extremely low during embryo transfer, even implantation cannot occur. 20 The data from the present study imply that luteal support with vaginal P alone seems inadequate in terms of P actions in a considerable proportion of women. As possible explanations for this, first, one may argue that there might be inter-individual variability in the absorption of P through the vaginal wall.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, if P levels are extremely low during embryo transfer, even implantation cannot occur. 20 The data from the present study imply that luteal support with vaginal P alone seems inadequate in terms of P actions in a considerable proportion of women. As possible explanations for this, first, one may argue that there might be inter-individual variability in the absorption of P through the vaginal wall.…”
Section: Discussionmentioning
confidence: 55%
“…Although highly speculative, peri‐implantation may be a P‐dependent critical period during which the pregnancy outcome is predetermined. However, if P levels are extremely low during embryo transfer, even implantation cannot occur 20 …”
Section: Discussionmentioning
confidence: 99%
“…Although having different timing in the P4 assessment, quite impressively, all the previous studies nearly showed the same outcome, having higher values of luteal P4 (>9 ng/ml) related to higher outcomes rate. More specifically, the consistency of these results goes beyond the timing in which progesterone was evaluated (day of FET, day before FET, or 11 days after FET, respectively, for 10 , 16 , 18 , 19 , 22 ). In fact, the common feature of all the results was that whenever P4 was in the lower limit, the cycle outcomes were hindered.…”
Section: Discussionmentioning
confidence: 69%
“…Progesterone has two key features: one is that pharmacokinetics depends on the route of administration and consequently the serum values (13); the other one is the daily variability (14,15). Despite the high variability of P4, all the recent studies published on luteal serum P4 showed that low serum levels of P4 (below 9-10 ng/ml) are associated with worse cycle outcomes (10,(16)(17)(18)(19)(20), independently from the day of the assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Once pregnancy is established, it appears that the higher the progesterone concentration, the more likely the pregnancy continues. A recent prospective cohort study [ 130 ] sought to evaluate potential differences in serum P levels throughout the late luteal phase (days 4, 7, and 11 after ET) based on pregnancy outcomes and reported that patients with an ongoing pregnancy had higher levels of serum P than the rest, particularly those with a negative result or pregnancy loss. And there was an increasing trend of serum P level throughout the luteal phase days.…”
Section: Methodsmentioning
confidence: 99%